FACILITATING COMMUNITY PARTICIPATION THROUGH CROWDSOURCING IN URBAN PLANNING PROCESSES: AN EXPLORATORY STUDY - Lindelwa Sinxadi (Journal of Construction Project Management and Innovation)
Fostering community participation by planners in South African municipalities poses a challenge during planning processes. Different levels of public apathy have been observed, and they continue to undermine the quest of municipalities to provide sustainable neighbourhoods. Also, value conflicts from different urban stakeholders resulting from this apathy can be ameliorated through improved participation of the communities in the planning processes. In bridging this gap, the paper seeks to explore different Crowdsourcing techniques to be employed in Mangaung to enable urban stakeholders’ participation in planning projects. As such, crowdsourcing, as a new web-based business model, is inclusive in the 4th Industrial Revolution and can be used as the best solution for community participation in planning projects.  Based on the foregoing, this paper employs a case study research design and a coterie of techniques: semi-structured interviews and document reviews for data elicitation. Interviewees comprise of purposively recruited town planning and other municipal officials involved in planning projects. The emergent data will be analysed thematically. Expectedly, the findings hold immense implications for planning practitioners as well as other professionals and policymakers working within the urban planning and socio-economic development praxes in South African Municipalities.